Effectiveness of Metformin in Management Latest Type 2 Diabetes Mellitus : A Literature Study - Hariaji, Ilham (Buletin Farmatera, 2025)
Abstract: Diabetes mellitus type 2 (DMT2) is a chronic metabolic disease whose prevalence is increasing globally. Metformin remains a first-line therapy due to its effectiveness in lowering blood glucose and its good safety profile. This literature review analyzed 25 publications from the journal Scopus Q1 (2021–2025) that evaluated the effectiveness of metformin in monotherapy and combination therapy. The studies analyzed included randomized controlled clinical trials, meta-analyses, and cohort studies. Metformin showed an average HbA1c decrease of 1.0–1.5%. Combination with SGLT2 inhibitors and GLP-1 receptor agonists improves glycemic control and lowers cardiovascular risk. Anti-inflammatory and endothelial protective effects have also been reported. Metformin remains relevant as the primary therapy, but its effectiveness increases when combined with new agents and adapted to the characteristics of the patient. Metformin is effective in the management of current DMT2, especially in combination therapy and personalization approaches.